A Composite Multi-Body Dynamics and Finite Element Framework for Offshore Wind Turbine Fatigue Assessment - McAuliffe, James Patrick (Trinity College Dublin. School of Engineering. Disc of Civil Structural & Environmental Eng, 2026)
The race to replace fossil fuels with renewable energy sources has intensified in response to the escalating threats of climate change. This urgency has driven unprecedented growth in the wind energy sector, leading to significant advancements in wind turbine technology. Over the past two decades, turbines have dramatically increased in both size and capacity, as the industry strives to maximise energy capture and position wind energy as a viable competitor to conventional fossil fuel-based generation. The development of offshore wind turbines has enabled access to the rich aeolian resources of the open sea, where higher wind speeds and improved airflow quality enhance power production. However, the increased scale and offshore location of modern, multi-megawatt wind turbines introduce complex structural and operational challenges. The growing length of turbine blades and corresponding tower heights has led to increasingly slender and flexible structures. These large-scale systems experience highly dynamic responses under the elevated aerodynamic and hydrodynamic loads characteristic of offshore environments. The rotating mass of the turbine blades, in an atmospheric boundary layer characterised by wind shear, further contributes to the operational demands of these systems, imposing substantial cyclic, gravitational forces on key structural components. Consequently, modern offshore wind turbines are subjected to intensified cyclic loading, often exceeding 100 million load cycles over a 20-year design life, while operating in the corrosive conditions of the marine environment. The combination of these factors makes wind turbines and their components highly susceptible to fatigue damage, directly impacting their operational lifespan. Accurately quantifying this damage is therefore essential for the effective design and analysis of offshore wind turbines. It enables the optimisation of maintenance schedules and end-of-life strategies, while also improving the accuracy of Levelised Cost of Energy (LCOE) calculations, ensuring both structural safety and economic viability. Recognising the critical importance of accurately quantifying fatigue damage, in this work a composite modelling framework is developed to perform an efficient and high-fidelity fatigue analysis of offshore wind turbines. The composite modelling framework employs a blended approach, integrating a multibody dynamic (MBD) model and a detailed finite element (FE) model, leveraging the strengths of both approaches to deliver an efficient and accurate fatigue analysis of the IEA 15-MW monopile-based offshore wind turbine. The nonlinear MBD model, developed previously within the research group, is fully coupled with 22 degrees of freedom (DOFs) and formulated using Kane's dynamics. This model captures the global dynamic response of the wind turbine under operational conditions, considering the effects of both hydrodynamic and aerodynamic loading. However, while the MBD model provides accurate system-level dynamics, its reliance on simplified geometric representations limits its ability to resolve localised stresses in critical turbine components such as bolts, welds, or flanges. To address this limitation, the resulting nominal stress time histories from the MBD model are enhanced by incorporating stress concentration factors (SCFs) derived from a high-fidelity FE model, enabling accurate consideration of local geometric effects. Employing this composite model framework, a fatigue analysis was performed considering real metocean conditions defined by the National Renewable Energy Laboratory (NREL) for a site off the east coast of the United States. The analysis focuses on a butt weld located at the base of the tower, a known fatigue-critical detail, with industry failures documenting its susceptibility to crack initiation. This butt weld connects the tower shell to an internally bolted ring flange which serves as the interface between the tower and the transition piece. By considering the stiffening effect of the internally bolted ring flange connection through the use of SCFs, the fatigue life of the butt weld was observed to decrease by 19.3% in comparison with traditional approaches which neglect such effects. This highlights the significant impact of local structural features on fatigue performance. Failing to account for such features can lead to non-conservative fatigue life estimates, increasing the risk of premature failures in wind turbine towers giving rise to both structural safety concerns and substantial financial losses. The fatigue analysis conducted was further extended to include the effects of the corrosive marine environment, reflecting material degradation over time. The parametric capabilities of the developed FE model were employed to capture the effects of material degradation caused by the corrosive marine environment, generating time-varying SCFs. By combining these SCFs with the nominal stress time histories and appropriate S-N curves, the model enhances fatigue damage predictions at the butt weld, accounting for scenarios in which corrosion protection measures have failed. When assuming a typical corrosion protection system that remains effective for the first five years of operation, the predicted fatigue life of the butt weld was reduced to 13.39 years. This fatigue life falls significantly short of the intended 20-year lifespan illustrating the vital importance of considering the effects of corrosion wastage on the lifespan of such critical components. Given that inspection and repair of these welds on offshore structures are both prohibitively expensive and operationally complex, accurately predicting their fatigue performance is essential to avoid unplanned maintenance, reduce operational risk, and ensure long-term structural reliability. The vulnerability of these welds to the corrosive marine environment was further demonstrated using the composite modelling framework to perform fatigue analyses for two sites off the coast of Ireland using environmental conditions obtained from the Irish Marine Data Buoy Observation Network (IMDBON). Under the same corrosion protection system, with failure assumed after five years, the fatigue lives were estimated to be 24.75 and 13.38 years for the east and west coast sites respectively demonstrating significant reductions as a result of the material wastage induced by corrosion. Additionally, these results reveal substantial variations in structural performance between the two sites, emphasising the necessity of site-specific design considerations. These findings collectively demonstrate the turbine's vulnerability to fatigue loading and underscore the need to effectively reduce fatigue demands on structural components, particularly in harsh offshore environments. To address the limited lifespans observed, vibration control devices, including a Tuned Mass Damper (TMD) and Tuned Mass Damper Inerter (TMDI), were installed at the top of the wind turbine tower. While both devices demonstrate significant vibration mitigation capabilities, their overall effectiveness in reducing fatigue damage is limited due to adverse interactions with non-targeted structural modes. As a result, neither the TMD nor the TMDI provided a significant improvement with regard to the fatigue performance for the offshore wind turbine tower. The findings of this thesis highlights the importance of integrated modelling approaches that account for both global dynamics and local stress concentrations, while also incorporating environmental degradation effects. The results emphasise the critical role of detailed fatigue assessment in offshore wind turbine design and the limitations of conventional mitigation strategies, reinforcing the need for more resilient solutions to ensure structural reliability and long-term economic viability.
APPROVED